Imaging of a Case of Extramedullary Solitary Plasmacytoma of the Trachea. (22nd September 2011) - Garelli, M.; Righini, C.; Faure, C.; Jankowski, A.; Brambilla, C.; Ferretti, G. R.
Abstract : We describe a case of extramedullary tracheal plasmacytoma that was incidentally discovered in a 73-year-old man on a PET scan performed for assessing the extent of colon cancer. CT scan showed the tumor; multiplanar reformation coupled with virtual bronchoscopy allowed proper treatment planning. The tracheal tumor was resected during rigid bronchoscopy. Relevant investigations excluded multiple myeloma. Follow-up CT showed persistent thickening of the tracheal wall, but there has been no recurrence after one-year followup.